Antibiotic Treatment Patterns in Conjunctivitis Patients based on Medical Records - Lilis Suryani; Ulfiyatul Afifah; Nur Shani Meida; Yunani Setyandriana (Journal La Medihealtico, 2026)
Conjunctivitis is the most common eye disease. The prevalence of conjunctivitis is influenced by gender, patient age, and season. This study aimed to determine the characteristics and patterns of antibiotic use among patients with conjunctivitis at PKU Gamping Hospital, Yogyakarta. This study design is descriptive. The sample size was 203 people, all outpatients treated at the Eye Clinic of PKU Muhammadiyah Gamping Hospital, Yogyakarta, from 2019 to 2021, who were diagnosed with conjunctivitis by an ophthalmologist. The instruments used in this study included a structured data collection form to record age, gender, education level, employment type, and the antibiotic therapy prescribed to patients, and the Chi-Square analysis to determine demographic variables as risk factors for conjunctivitis. The Ethics Committee has approved this study with approval number 217/EC-KEPK FKIK UMY/VIII/2020. There are more males than women; most people with conjunctivitis are under 20 years old (39.9%), have a high school education (37%), and work indoors (93%). The Chi-Square analysis test showed that age, education level, and type of work are risk factors for the characteristics of conjunctivitis (p<0.05). Meanwhile, gender is not a risk factor for conjunctivitis (p>0.05). The antibiotics most frequently used to treat conjunctivitis patients were Neomycin Sulfate (24.9%), Polymyxin B (21.5%), Ofloxacin (17.1%), Levofloxacin (8.9%), and Chloramphenicol (5.1%), respectively. The study shows that age, educational level, and occupation are risk factors for conjunctivitis in Yogyakarta. Certain age groups, lower education levels, and vulnerable types of work are at higher risk of developing conjunctivitis.